(untitled) (Bangladesh Journal of Pharmacology, 2015)
In this investigation, a scanning electron microscopy (SEM) method was used to examine the morphostructural changes in bacterial cells induced by antimicrobial agents. SEM-based visual approach is referred the study of bacterial cells and their physiological consequences when affected by antibiotics or antibacterial agents permitting the observation of characteristic morphological defects of cell wall, and provides valuable insights into processes involved in bacterial cell death. This experiment visualized various step-by-step techniques used in the slide preparation of bacterial cells treated with specific antimicrobial agent for analyzing the morphological alterations such as increase of cell wall roughness, cell disruption, cell swelling and lysed cell formation due to loss of intracellular material using SEM analysis when compared with untreated normal cells as a control. The SEM approach used in this visual experiment may analyze the antimicrobial effect of any commercially known or new compounds in a very conducive manner. Video Clips of Methodology: Culturing of bacteria: 2 min 54 sec Full Screen Alternate Treatment of bacterial culture by antimicrobials: 4 min 21 sec Full Screen Alternate Sample pre-treatment: 4 min 23 sec Full Screen Alternate Microscopic slide preparation: 9 min 27 sec Full Screen Alternate Critical point drying and ion sputter coating of slides: 5 min 52 sec Full Screen Alternate Scanning Electron Microscopic analysis of coated slides: 4 min 18 sec Full Screen Alternate